Cognitive booster of wampee peel extract on chronic restraint stress-induced memory dysfunction in rats - Terdthai Tongun, Wathita Phachonpai (Journal of Applied Pharmaceutical Science, 2020)
Novel antioxidants and acetylcholinesterase (AChE) inhibitors from fruits’ peel could be valuable alternatives for anti-amnesia. Wampee (WP) fruits are a rich source of high antioxidants. A lack of scientific document supports the efficacy of WP peel extract to ameliorate the memory impairment against amnesia induced by chronic restraint stress (CRS) until now. This study intended to illuminate the cognitive enhancer effect of WP peel extract in a rat model of CRS. The Wistar rats were treated with the WP peel extract (200, 400, and 600 mg/kg) in a restrainer for 4 hours for 28 consecutive days. The object recognition and Morris water maze tests were used to evaluate cognitive performances. The lipid peroxidation, AChE inhibitory, and scavenging enzyme activities in the rat's brain were also investigated. CRS exposure induces oxidative stress, decreases the antioxidant enzymes but increases AChE activities, and causes memory deficit in cognitive tests. Hence, all various doses of WP peel extract were able to significantly diminish chronic stress-induced memory deficit, attenuated the brain deterioration originated by an excessive oxidative stress, and show a capacity to inhibit AChE enzyme activity. These findings indicate that WP peel extract was safe and valuable functional ingredients to develop the product for brain-boosting foods.
Keywords: Wampee, cognitive booster, oxidative damage, stress, brain-boosting foods.